Local government size and service level provision. Evidence from conditional non-parametric analysis. (June 2022) - D'Inverno, Giovanna; Moesen, Wim; De Witte, Kristof
Abstract: Although the local provision of public goods accommodates better to the heterogeneous local preferences and mitigates the fiscal illusion problem, it comes at the cost of potential diseconomies of scale. This paper examines the relationship between municipal size and local service level provision by applying state-of-the-art non-parametric techniques to a unique panel dataset of Flemish data. We measure the service provision level by using an innovative robust conditional 'Benefit of the Doubt' model and we estimate its efficiency in relationship with the local expenditures by means of a robust conditional Data Envelopment Analysis model. Overall, the main findings suggest the presence of diseconomies of scale, and provide weak evidence on an optimal size of local public good provision of around 10, 000 citizens. Highlights: We examine the relationship between municipal size and local service provision. State-of-the-art non-parametric techniques are applied to Flemish municipalities. Service provision is measured by an original robust conditional composite indicator. Municipal expenditure efficiency is assessed by a robust Data Envelopment Analysis. Results denote scale diseconomies and optimal size around 10, 000 citizens.